Campus election runs smoothly, concurrently in Gambang & Pekan - UMP, PNC
Universiti Malaysia Pahang's (UMP) campus election ran smoothly without a hitch, with 4,596 students, or about 75% of the university’s population, filling their ballot papers at the two campuses in Gambang and Pekan.